2003
DOI: 10.1081/clt-120025358
|View full text |Cite
|
Sign up to set email alerts
|

A Fatal Case of Spongiform Leukoencephalopathy Linked to “Chasing the Dragon”

Abstract: The diagnosis of heroin pyrolysate-induced spongiform leukoencephalopathy should be considered in a patient with a history of "chasing the dragon" and neurobehavioral changes, including confusion, apathy, cerebellar signs, and motor restlessness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 15 publications
0
17
0
1
Order By: Relevance
“…The first and largest outbreak of leukoencephalopathy linked to chasing the dragon was reported 1982 in the Netherlands, and included 47 cases, 11 (23%) of whom died [6]. Since 1982, sporadic cases and small case clusters (ranging from 1-4 cases) have been report ed in Taiwan [7,8], Hong Kong[9], other European countries [4,5,10-13], the United States [3,14,15] and Canada [16]. Three larger clusters have been identified in China [17-20].…”
Section: Introductionmentioning
confidence: 99%
“…The first and largest outbreak of leukoencephalopathy linked to chasing the dragon was reported 1982 in the Netherlands, and included 47 cases, 11 (23%) of whom died [6]. Since 1982, sporadic cases and small case clusters (ranging from 1-4 cases) have been report ed in Taiwan [7,8], Hong Kong[9], other European countries [4,5,10-13], the United States [3,14,15] and Canada [16]. Three larger clusters have been identified in China [17-20].…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidant agents including coenzyme Q, vitamin C, and vitamin E have been suggested to provide a varying degree of benefit in patients with toxic leukoencephalopathy knowing their safe profile adverse effect [ 4 , 15 - 18 ]. In our first case, antioxidant treatment did not improve symptoms, whereas in our second case, it resulted in remarkable improvement.…”
Section: Discussionmentioning
confidence: 99%
“…A specific type of encephalopathy, toxic spongiform leukoencephalopathy (HSL, heroin inducted spongiform leukoencephalopathy), is observed in users that ingest heated vapours . This disorder has a high mortality rate and has been discussed in several studies dating from the 1980s to the present . One report showed changes in brain tissues using MRI and suggested that the mechanism of toxicity for HSL is related to impaired cellular metabolism .…”
Section: Diacetylmorphine (Heroin)mentioning
confidence: 99%